COUNTER DISCOURSE OF MACULINITY IN AVENGER: END GAME MOVIE - Agustin Diana Wardaningsih; E. Ngestirosa Endang Woro Kasih (Faculty of Arts and Education, 2022)
AbstractMasculinity in mass communication always attracts attention and is a hot topic of discussion. The masculinity of men who are always juxtaposed with women is a power struggle on two sides: men as men themselves and men compared to women. The study aims to counter the dominant masculinity issue in Avenger: The End Game (2018) movie. This study sheds light on the position of men in superhero films who are always dominant in masculinity. However, this film also shows declining male masculinity where men show their powerless side. This study was conducted with a descriptive qualitative method. Stuart Hall's representation theory and Chafetz's masculinity are the main theories to dissect male masculinity. Secondary data from other journals and books also supported the analysis. Finding and analysis finally show that men's powerless and men's emotions become male declining masculinity in this film.Keywords: communication, declining, domination, male, masculinity